PENERAPAN POLA ASUH ORANG TUA DALAM MENUMBUHKAN KEMANDIRIAN PADA ANAK USIA DINI - Rita Nofianti (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2018)
The application of parenting parents against early childhood when growing the independence of early childhood, especially self-reliance when at home. This research aims to know to what extent about the application of parents in growing the independence of early childhood, this is done because today there are many cases of the understanding of the parents ' foster pattern that is less obvious in understand by Parents, and finally the child who became his champion. Especially early childhood. This method of foster democracy uses explanations, discussions, and reasoning, to help the child understand why certain behaviors are expected. Especially for each parent should be aware of the pattern of foster, type and variety, so that when at home or when meeting with the child is good at putting a foster-like pattern for each child. So that the child is more directed and more confident when in school, because they have been supplied by his own parents. Parents need the education of early childhood because they think that the foster pattern in the family is one of the primary educational pathways of school, where in the family education there is a process The learning done by parents and children, the more the complexity of today's life, the family education in this case the foster pattern applied by parents to early childhood is increasingly important.